Pengembangan Media Flashcard Match a Picture Berbasis Literasi Sains Pada Materi Melihat Karena Cahaya Meningkatkan Higher Order Thinking Skills : (Development of Flashcard Match a Picture Media Based on Scientific Literacy on Light and Vision Materials to Improve Higher Order Thinking Skills) - Yuwafi , Mohammad Khamdan; Alfi , Cindya; Fatih , Mohamad (BIODIK, 2025)
This research aims to develop a Flashcard Match A Picture learning medium grounded in scientific literacy on the topic “Seeing Because of Light” to enhance Higher Order Thinking Skills (HOTS) among fifth-grade elementary students. The study employed a Research and Development (R&D) approach with a 4D model consisting of the define, design, develop, and disseminate stages. The participants were fifth-grade students of SDN Karangrejo 04, Blitar Regency. The results of the feasibility test indicated that the media obtained 91.6% from the material validator and 92.5% from the media expert, both classified as highly feasible. Limited trials revealed an improvement in students’ HOTS with an N-Gain score of 0.9, categorized as high. These findings suggest that the scientific literacy–based Flashcard Match A Picture medium is effective in enhancing students’ higher-order thinking skills. Abstrak. Penelitian ini bertujuan untuk mengembangkan media pembelajaran Flashcard Match A Picture berbasis literasi sains pada mata pelajaran IPAS materi ‘Melihat karena Cahaya’ untuk meningkatkan Higher Order Thinking Skills (HOTS) siswa kelas V SD. Jenis penelitian ini menggunakan metode Research and Development (R&D) model 4D yang meliputi tahap define, design, develop, dan disseminate. Subjek penelitian ini adalah siswa kelas V SDN Karangrejo 04 Kecamatan Garum Kabupaten Blitar. Hasil dari validasi ahli media menunjukkan nilai kelayakan sebesar 91,6% dan ahli materi sebesar 92,5%, yang termasuk kategori sangat layak. Uji coba terbatas menunjukkan peningkatan kemampuan HOTS siswa dengan skor N-Gain sebesar 0,9 dalam kategori tinggi. Hasil penelitian ini menunjukkan bahwa media flashcard match a picture berbasis literasi sains efektif untuk meningkatkan kemampuan berpikir tingkat tinggi siswa.